Developing a learning progression for three‐dimensional learning of the patterns of evolution. Issue 5 (21st June 2017) - Wyner, Yael; Doherty, Jennifer H.
Abstract: This paper examines how students make progress toward three‐dimensional (3D) understanding of the patterns of evolution. Specifically, it proposes a learning progression that explains how scientific practices, crosscutting concepts, and disciplinary core ideas come together in naming and grouping, length of change over time, and the role of common ancestry in evolutionary relatedness. To develop this learning progression, we created a 3D plant evolution curriculum for urban middle school students and over two implementation cycles we measured student understanding before, during, and after use of the curriculum. We used an iterative design, grounded in evidence of student learning over time to develop and revise our learning progression framework, assessments, and curriculum. The learning progression developed through this process is a template for conceptual learning through scientific practice, the type of 3D learning advocated by the Next Generation Science Standards. This paper describes the interplay between scientific practice learning and conceptual learning and the implications of this research for curriculum and assessment design.